Additions to orchid flora of Bhutan III: Paphiopedilum × pradhanii - Dorji, Phub; Gyeltshen, Phub; Tobgay, Kezang; Dorji, Sherab; Dorji, Ugyen; Doya, Sha Kinley; Kumar, Pankaj (Lankesteriana: International Journal on Orchidology, 2023)
Paphiopedilum × pradhanii, a natural hybrid between P. fairrieanum (subgenus Paphiopedilum, section Ceratopetalum) and P. venustum (subgenus Paphiopedilum, section Barbata), is reported for the first time from Bhutan. Detailed geographical distribution, ecology, and conservation status, and dichotomous keys to all Paphiopedilum species found in Bhutan are provided. A brief description of the parents of this hybrid is also provided.